2022
DOI: 10.1080/1331677x.2022.2106270
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial development and foreign direct investment on environmental sustainability in Sub-Saharan Africa: using PMG-ARDL approach

Abstract: This study is aimed at establishing the impact of foreign direct investment and financial development on carbon dioxide emission and clean energy using 44 countries in sub-Saharan Africa ranging from 1998 to 2017. Employing a second generation unit root test in conjunction with Pooled Mean Group, the study established that financial development have significant positive impact on clean energy consumption in sub-Saharan Africa. This was found to be consistent in both low-income and middle-income countries in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…Financing renewable energy consumption, green technological innovations, energy efficiency, and research and development projects will enhance ecological sustainability in East Africa because such activities are not pollution-intensive. This finding contrasts with the study of Nyeadi (2023) that reported financial development as useful to the environment of middle-income economies in sub-Saharan Africa. The finding also conflicts with the studies of Safi et al (2021) for 10 polluted economies, Abro et al (2022) for Saudi Arabia, and Tao et al (2023) for OECD economies.…”
Section: Discussion Of the Resultscontrasting
confidence: 99%
“…Financing renewable energy consumption, green technological innovations, energy efficiency, and research and development projects will enhance ecological sustainability in East Africa because such activities are not pollution-intensive. This finding contrasts with the study of Nyeadi (2023) that reported financial development as useful to the environment of middle-income economies in sub-Saharan Africa. The finding also conflicts with the studies of Safi et al (2021) for 10 polluted economies, Abro et al (2022) for Saudi Arabia, and Tao et al (2023) for OECD economies.…”
Section: Discussion Of the Resultscontrasting
confidence: 99%
“…The ARDL methodology is the most often used methodology for similar studies. We used the same steps as (Attiaoui and Boufateh, 2019;Hotak et al, 2020;Nyeadi, 2023), who constructed their empirical application starting with the firstgeneration unit root tests and then cointegration tests (such as Pedroni and Kao, 1999) and the PMG model. Hotak et al (2020) state that the reason for using the PMG model is "in addition, the possible correlation between the mean-differenced independent variables and the white noise term may cause standard autoregressive distributed lag (ARDL) models to suffer from biased estimators in panel data models with fixed effects.…”
Section: Model and Methodologymentioning
confidence: 99%
“…Also, FDI has become a critical cause of private external finance for developing economies. According to the literature, FDI can possibly be channelled from strict environmental economies to divert their production to SACU countries if they have weak environmental policies (Copeland and Taylor (1994) and Nyeadi (2023)). In addition, FDI is considered from the view that SACU countries are still developing countries and to grow their economies, they have weak foreign investment policies that may possibly attract investments that are not environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%